The imbalance in the relationship between inflammatory and regulatory cytokines during gestational toxoplasmosis can be harmful to fetuses: A systematic review - Santos, Priscilla Vilela dos; Toledo, Débora Nonato Miranda de; de Souza, Débora Maria Soares; Menezes, Tatiana Prata; Perucci, Luiza Oliveira; Silva, Zolder Marinho; Teixeira, Daniela Caldas; Vieira, Ed Wilson Rodrigues; Andrade-Neto, Valter Ferreira de; Guimarães, Nathalia Sernizon; Talvani, André (Frontiers in Immunology, 2023)
Objective To evaluate the available information on inflammatory and regulatory plasma mediators in pregnant women (PW) diagnosed with toxoplasmosis. Source: The PubMed, Embase, Scopus, and Lilacs databases were evaluated until October 2022. Study eligibility criteria: This review was carried out following the PRISMA and registered on the PROSPERO platform (CRD42020203951). Studies that reported inflammatory mediators in PW with toxoplasmosis were considered. Evaluation methods After excluding duplicate articles, two authors independently carried out the process of title and abstract exclusion, and a third resolved disagreements when necessary. The full text was evaluated to detect related articles. The extraction table was built from the following data: Author, year of publication, journal name and impact factors, country, study design, number of gestations and maternal age (years), gestational period, diagnosis of toxoplasmosis, levels of inflammatory markers, laboratory tests, and clinical significance. Methodological quality was assessed using Joanna Briggs Institute tools. Results Of the 1,024 studies reported, only eight were included. Of the 868 PW included in this review, 20.2% were IgM+/IgG- and 50.8% were IgM-/IgG+ to T. gondii, and 29.0% uninfected. Infected PW presented higher plasma levels ofIL-5, IL-6, IL-8, IL-17, CCL5, and IL-10. Regarding the methodological quality, four studies obtained high quality. Data from this review pointed out the maintenance of the inflammatory pattern during pregnancy with a closely related to the parasite. Conclusion Immune status in PW defined the course of the T. gondii infection, where the equilibrium between inflammatory and regulatory cytokines mitigated the harmful placenta and fetus effects. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD420203951.